1967
DOI: 10.1085/jgp.50.5.1353
|View full text |Cite
|
Sign up to set email alerts
|

NMR Evidence for Complexing of Na+ in Muscle, Kidney, and Brain, and by Actomyosin. The Relation of Cellular Complexing of Na+ to Water Structure and to Transport Kinetics

Abstract: The nuclear magnetic resonance (NMR) spectrum of Na + is suitable for qualitative and quantitative analysis of Na + in tissues. The width of the N M R spectrum is dependent upon the environment surrounding the individual Na + ion. N M R spectra of fresh muscle compared with spectra of the same samples after ashing show that approximately 70 % of total muscle Na + gives no detectable N M R spectrum. This is probably due to complexation of Na + with macromolecules, which causes the N M R spectrum to be broadened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

1968
1968
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(34 citation statements)
references
References 30 publications
3
30
0
1
Order By: Relevance
“…The 23Na signal drop is therefore not attribut able to changes in relaxation time caused by ischemia. It is considered that this drop in 23Na signal intensity may result from movement of23Na into the intracellular space, as 60-70% of the intracellular 23Na in the brain seems to be invisible by NMR methods (Cope, 1967). In this study, the remarkable drop in 23Na signals intensity was thought to reflect disruption of the N a + pump activity.…”
Section: Analysis Of 23na Signal Changesmentioning
confidence: 65%
“…The 23Na signal drop is therefore not attribut able to changes in relaxation time caused by ischemia. It is considered that this drop in 23Na signal intensity may result from movement of23Na into the intracellular space, as 60-70% of the intracellular 23Na in the brain seems to be invisible by NMR methods (Cope, 1967). In this study, the remarkable drop in 23Na signals intensity was thought to reflect disruption of the N a + pump activity.…”
Section: Analysis Of 23na Signal Changesmentioning
confidence: 65%
“…(b) Na is fixed to the substance which fills the intercellular space (Farquhar & Palade, 1965).This space is opened toward the inside permitting a ready exchange with the inner solution, but closed on the outside by the maculae occludens. The large extent of complexing of Na in living tissues is a very well-known phenomenon in many other tissues (Shaw & Simon, 1955;Ling, 1962;Troshin, 1966;Cope, 1967). In fresh muscle, for instance, only 30 % of the Na is detectable by nuclear magnetic resonance analysis (Cope, 1967).…”
mentioning
confidence: 99%
“…The large extent of complexing of Na in living tissues is a very well-known phenomenon in many other tissues (Shaw & Simon, 1955;Ling, 1962;Troshin, 1966;Cope, 1967). In fresh muscle, for instance, only 30 % of the Na is detectable by nuclear magnetic resonance analysis (Cope, 1967). Therefore, if the intercellular space were filled with an ion binding substance, it would not be surprising that it would show the properties assigned to the ENTC.…”
mentioning
confidence: 99%
“…Measurements of the 39K NMR signal in biological tissues (1)(2)(3)(4) have shown that not all the potassium present is detectable when compared to chemical analysis methods such as atomic emission or absorption spectroscopy. Many of these studies showed the relative amount of potassium detected, commonly termed NMR visibility, to be around 40%, although there was some variability between tissues (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies showed the relative amount of potassium detected, commonly termed NMR visibility, to be around 40%, although there was some variability between tissues (1)(2)(3)(4). The 40% visibility figure has been rationalized as consistent with certain spectral characteristics arising from the quadrupolar relaxation of this spin-; nucleus.…”
Section: Introductionmentioning
confidence: 99%